2016
DOI: 10.1097/cin.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Need to Integrate Academic Electronic Medical Records Into the Undergraduate Clinical Practicum

Abstract: As healthcare systems demand that nurses be competent in using electronic medical records for patient care, the integration of electronic medical records into nursing curricula has become necessary. The purpose of this study was to explore how students, new nurses, clinical instructors, and faculty perceive the integration of academic electronic medical records into the undergraduate clinical practicum. From January to February 2014, four focus group interviews with 18 participants were conducted based on purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Simulated EHRs for academic purposes have been proposed as an innovative pedagogy to promote the acquisition of theoretical knowledge of informatics and the skills needed to use EHRs in a safe environment before encounters with real patients [14][15][16][17][18][19][20][21][22][23][24][25]. Incorporating these learning experiences within undergraduate nursing education expands the realm of effective teaching and learning practice, fulfills accreditation requirements, and ensures graduates have the required entry-to-practice competencies in nursing informatics upon exiting the program so that they are better prepared for practice in today's digitally rich health care environment [3,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulated EHRs for academic purposes have been proposed as an innovative pedagogy to promote the acquisition of theoretical knowledge of informatics and the skills needed to use EHRs in a safe environment before encounters with real patients [14][15][16][17][18][19][20][21][22][23][24][25]. Incorporating these learning experiences within undergraduate nursing education expands the realm of effective teaching and learning practice, fulfills accreditation requirements, and ensures graduates have the required entry-to-practice competencies in nursing informatics upon exiting the program so that they are better prepared for practice in today's digitally rich health care environment [3,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers found that simulated EHRs help enhance students' skills in electronic documentation [24,41,42] and aid in the development of positive attitudes and perspectives about electronic records [43,44]. The integration of simulated EHRs also enhances students' confidence and self-efficacy in using electronic records [23,[44][45][46] and increases informatics knowledge and competency [16,40,47]. Despite these benefits, factors such as cost and faculty expertise continue to be major challenges in integrating simulated EHRs in nursing education [18,34,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of EMR into the curriculum, both theory and simulation learning, would better prepare them for the real world of clinical practice. EMR systems and educational programs have been successfully integrated into undergraduate nursing curriculum in other countries such as USA, 19,21,41 Canada, 10 South Korea, 7,18 and Singapore, 24 however it is unclear why there has been a delayed interval in Australian universities. The Australian Nursing and Midwifery Accreditation Council (ANMAC) accreditation standards makes specific mention of prioritising the development and application of knowledge and skills in health informatics and health technology in the undergraduate nursing program content.…”
Section: Discussionmentioning
confidence: 99%
“…16 Healthcare organisations are wanting nurses to be skilled in the use of the technology and information management relating to patient care. 18 However, it is recognised that using EMR systems can be time consuming tasks for new nurses as they assimilate into the healthcare system. 11 To successfully implement a specific academic EMR program, it is recommended that integration is done in five stages: planning, product demonstration, faculty development and training, curriculum threading and implementation and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation